Psychophysical Benefits of Rock-Climbing Activity. Issue 3 (December 2015) - Gallotta, Maria Chiara; Emerenziani, Gian Pietro; Monteiro, Maria Dolores; Iasevoli, Luigi; Iazzoni, Sara; Baldari, Carlo; Guidetti, Laura
The aim of the study was to compare the psychophysical effects of rock climbing with a supervised fitness training in adults. Thirty-three healthy participants ( M age = 32yr., SD = 7) participated in rock climbing or in fitness training. The participants' functional fitness, anxiety, and mood states were tested before and after 3 mo. of training. There was significant improvement of physical fitness in both groups after the intervention period. Anxiety significantly decreased after each single training session at the end of both courses. Differential effects in the rock-climbing group, as compared to the fitness group, emerged only on Vigor. Specifically, the rock-climbing group showed a decreasing trend in Vigor while the fitness group showed an increasing trend of Vigor after the intervention.